1995
DOI: 10.1128/jvi.69.3.1810-1818.1995
|View full text |Cite
|
Sign up to set email alerts
|

Syncytium-inducing (SI) phenotype suppression at seroconversion after intramuscular inoculation of a non-syncytium-inducing/SI phenotypically mixed human immunodeficiency virus population

Abstract: Two distinct biological phenotypes of human immunodeficiency virus (HIV) have been described: the non-syncytium-inducing (NSI) phenotype, best characterized by the inability to infect MT-2 cells, and the syncytium-inducing (SI) phenotype, with the ability to infect MT-2 cells. The earliest virus population observed following HIV transmission is generally of the NSI phenotype, even after exposure to inocula of mixed NSI/SI phenotype. In this study, the issue of intrapatient selection of virus phenotype followin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
57
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 158 publications
(61 citation statements)
references
References 58 publications
4
57
0
Order By: Relevance
“…For example, some similarities can be observed between the findings of the present study and a previous study that assessed co-receptor tropism of HIV-1 strains in China: mainly that R5 tropism was seen exclusively in subtype C infections, and remained stable over time [24]. These data highlight the persistence of CCR5 tropism even in long-term infections, possibly related to differences within the env variable loops [37], and contrasts with other subtypes, especially subtype B, where X4 HIV-1 is more frequent during later stages of infection [6,[8][9][10]16,18,21,[37][38][39][40].…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…For example, some similarities can be observed between the findings of the present study and a previous study that assessed co-receptor tropism of HIV-1 strains in China: mainly that R5 tropism was seen exclusively in subtype C infections, and remained stable over time [24]. These data highlight the persistence of CCR5 tropism even in long-term infections, possibly related to differences within the env variable loops [37], and contrasts with other subtypes, especially subtype B, where X4 HIV-1 is more frequent during later stages of infection [6,[8][9][10]16,18,21,[37][38][39][40].…”
Section: Discussionsupporting
confidence: 62%
“…Studies of HIV-1 co-receptor tropism, which have been conducted primarily in populations where subtype B infections predominate, have demonstrated a relationship between HIV-1 co-receptor use and disease stage. In general, early stages of infection and disease are characterized by greater prevalence of only C-C chemokine type 5 (CCR5)-tropic (R5) HIV-1, which has been associated with slower progression to AIDS [8][9][10][11][12]. The emergence of C-X-C chemokine receptor type 4 (CXCR4)-using virus (X4) has been associated with greater treatment experience and higher risk of death, and coincides with more rapid CD4 + T-cell depletion and disease progression [6,8,9,12,13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The extent to which HIV infects and replicates in these various cell populations has important implications when considering the known effects of HIV gene expression on the function of various cell types (5,37) and the therapeutic potential of blocking cell type specific coreceptors required for HIV infection (1,10). In addition, different HIV-infected cell populations are important during disease transmission and dissemination from portals of entry (8,41) versus disease progression (7). Also, given the finite number of target cells for HIV infection, knowledge of the specific infected cell types in addition to plasma free virus levels will be important in understanding disease progression (23).…”
mentioning
confidence: 99%
“…Several studies have demonstrated that mixtures of viruses with different phenotypes are always circulating in an infected patient [6]. Viruses with the NSI phenotype are predominant in individuals with early or stable HIV infection, but some SI viruses are almost invariably present [33,34]. As HIV infection progresses, the initially dominant NSI viruses are usually replaced by SI viruses [6].…”
Section: Discussionmentioning
confidence: 99%